Argumentaire pour le français au Portugal et orbi : arguments, apories et représentations - Almeida, José Domingues de (2014)
The author proposes a broad reflection about the elaboration of a promotional flyer in favour of French foreign language learning and the role it plays in Portuguese context, and elsewhere in globalized context